IMPLEMENTASI PENDIDIKAN NILAI-NILAI MORAL DALAM PEMBELAJARAN PKN DI SDK ONEKORE 1 - Sadipun, Berty; Novianti, Chatarina (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The aim of this research is: To describe how moral values education is implemented in Civics learning at SDK Onekore 1 Hayam Wuruk. This research uses a descriptive qualitative approach. Data collection in this research was obtained through observation, interviews and documentation. Data analysis in this research uses qualitative data analysis techniques which include data collection, data presentation, and drawing conclusions. The results of the research show that: (1) Implementation of moral values in learning Pancasila and citizenship education, namely the values of discipline, honesty, religion, independence, responsibility, democracy, love of the country, and social care and demonstrated through attitudes or behavior that reflect these values. Moral values. (2) Factors supporting the implementation of moral values in citizenship education learning include the condition of the environment around the school, role models and habits, as well as meetings between educators and parents. Meanwhile, the inhibiting factors are the absence of educators, lack of parental attention, and excessive use of gadgets